Once upon a time - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The remains of what is thought to be the oldest settled African agricultural community have been discovered on the outskirts of Asmara, capital of Eritrea. On the basis of excavations and discovered artefacts, such as needles, gold earrings and farm...